Celebrating the James Partridge Award : essays toward the development of a more diverse, inclusive, and equitable field of library and information science - Barlow, Diane L.; Jaeger, Paul T., 1974- (Emerald Group Publishing Limited, 2016)
Celebrating the James A. Partridge Outstanding African American Information Professional Award the authors examine issues of race, inclusion, diversity, and justice in the field of library and information science. The award recognizes information professionals who exemplify the highest ideals of the profession, and it is part of a long-running series of efforts that have been made to promote diversity and inclusion in the field. Many of the living winners of the award share their thoughts and personal experiences about race and the development of the field of library and information science. Their insights are complimented by the writings of other scholars, educators, and practitioners who study, teach about, and experience issues of race in the field firsthand. Issues of race are addressed from the perspective of different backgrounds, as well as intersectionalities with other identities, such as gender, immigration, and orientation. The explorations by the authors at their various institutions including libraries, universities, and government agencies to promote diversity and inclusion catalogue a wide range of ideas, practices and lessons learned.
Keywords: Minorities in library science.; Minority librarians.; elektronické knihy; electronic books